Health‐related quality of life and symptoms in patients with myelofibrosis treated with ruxolitinib versus best available therapy. (14th May 2013) - Harrison, Claire N.; Mesa, Ruben A.; Kiladjian, Jean‐Jacques; Al‐Ali, Haifa‐Kathrin; Gisslinger, Heinz; Knoops, Laurent; Squier, Margaret; Sirulnik, Andres; Mendelson, Estella; Zhou, Xiaolei; Copley‐Merriman, Catherine; Hunter, Deborah S.; et al.
Summary Patients with myelofibrosis (MF) have significant debilitating symptoms, physical disabilities, and poor health‐related quality of life (HRQoL). Here, we report post‐hoc analyses of the impact of ruxolitinib, a potent and selective JAK1 and JAK2 inhibitor, on disease‐related symptoms and HRQoL in MF patients from the large phase 3 COMFORT‐II study (N = 219). During the follow‐up period of 48 weeks, HRQoL and MF‐associated symptoms improved from baseline for ruxolitinib‐treated patients but remained the same or worsened for best available therapy (BAT)‐treated patients. Based on the European Organization for Research and Treatment of Cancer QoL Questionnaire core 30 items (EORTC QLQ‐C30), treatment‐induced differences in physical and role functioning, fatigue, and appetite loss significantly favoured ruxolitinib versus BAT from week 8 (P < 0·05) up to week 48 (P < 0·05). Ruxolitinib resulted in significantly higher response rates in global health status/QoL and Functional Assessment of Cancer Therapy‐Lymphoma (FACT‐Lym) summary scores versus BAT at most time points (P < 0·05). Significant improvements in the Lymphoma subscale (including symptoms of pain, fever, itching, fatigue, weight loss, loss of appetite, and other patient concerns), FACT‐General, FACT‐Lym trial outcome index, and FACT‐Lym total were also observed with ruxolitinib versus BAT starting at week 8 and continuing thereafter. Overall, these data demonstrated that ruxolitinib improved HRQoL in MF patients and further support the use of ruxolitinib for the treatment of symptomatic MF.